2008
DOI: 10.1103/physrevd.78.083515
|View full text |Cite
|
Sign up to set email alerts
|

Delicatef(R)gravity models with a disappearing cosmological constant and observational constraints on the model parameters

Abstract: We study the f (R) theory of gravity using metric approach. In particular we investigate the recently proposed model by Hu-Sawicki, Appleby − Battye and Starobinsky. In this model, the cosmological constant is zero in flat space time. The model passes both the Solar system and the laboratory tests. But the model parameters need to be fine tuned to avoid the finite time singularity recently pointed in the literature. We check the concordance of this model with the H(z) and baryon acoustic oscillation data. We f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 133 publications
2
61
0
Order By: Relevance
“…If α = 0 and x = h − 3 (this case corresponds to the cases (1)- (6) presented above), we find 28) which is equivalent to Eq. (4.20) with α 1 = α 2 = 0.…”
Section: The Solution Of F (R G) Is Given Bymentioning
confidence: 98%
“…If α = 0 and x = h − 3 (this case corresponds to the cases (1)- (6) presented above), we find 28) which is equivalent to Eq. (4.20) with α 1 = α 2 = 0.…”
Section: The Solution Of F (R G) Is Given Bymentioning
confidence: 98%
“…It is well known that f (R) theories can be considered as equivalent scalar-tensor theories. It is easy to visualise curvature singularity in a f (R) theory by looking at the form of the potential appearing in its equivalent scalar-tensor theory in the Jordan frame [19]. Due to the nonlinear motion of the scalar field, the oscillations around the potential minimum can make the field displaced to the singular point.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that past singularities may be prevented for a certain range of parameters. These singularities may also occur in future and can be avoided for fine-tuned initial conditions [19,23]. It is also realised that the curvature singularities can be eliminated by adding an extra curvature term to the Lagrangian [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…This problem arises due to the dynamics of the effective scalar degree of freedom, χ, in the high curvature regime. Therefore, the problem may be cured by adding higher curvature corrections that modify the structure of the potential around the large R region, as already noted in the original reference [13] and later discussed in [27]. In general, higher curvature corrections may be written as a 2 R 2 + a 3 R 3 + · · · , and so the most natural choice of the leading order term will be R 2 /µ 2 .…”
Section: Adding Higher Curvature Corrections To F (R) Gravitymentioning
confidence: 99%
“…This is done again by constructing relativistic star solutions. A higher curvature correction changes the structure of the effective potential for the scalar degree of freedom around the singularity [13,27]. We consider a modified version of Starobinsky's f (R) [13], adding a correction term proportional to R m (m ≥ 2).…”
Section: Introductionmentioning
confidence: 99%